PROMOTING GROWTH OF SOCIAL ENTREPRENEURSHIP: POLICY FOR SUPPORTING MICRO AND SMALL ENTERPRISES - Pupung Purnamasari; Erwin; Andi Hafidah; Hadenan Towpek (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Due to the fact that it creates new job openings and employment prospects, entrepreneurship is crucial to the nation's economy. Entrepreneurship naturally creates job chances for the unemployed, therefore anyone running a significant firm requires staff to assist in running their business. This is the relationship between entrepreneurship and economic growth. Micro and Small Enterprises are an important part of the country's economy because they have made a major contribution to boosting the economy, including their contribution in opening up new job opportunities as a spur to economic growth and as a source of innovation. The government and society have fully seen the role and contribution of MSE entrepreneurs. With a very large contribution to Gross Domestic Product (GDP), of course MSEs can demonstrate their role as the backbone of the economy. The research methodology employed in this work is library study, which consists of a number of tasks related to how to gather data from libraries, read and take notes, and process research materials. This research discusses the concept of entrepreneurship, the role of micro and small businesses, and micro and small business support policies.